Pengembangan kombinasi produk keramik dan bambu sebagai dekorasi interior modern - Tiara Ika Widia Primadani; Wahyu Waskito Putra; Bambang Kartono Kurniawan; Mahendra Wardhana (Institut Seni Indonesia Yogyakarta, 2022)
Micro, small and medium enterprises (MSME) craftsmen need product innovation to develop and adapt to market developments. This study aims to diversify the products of ceramic and bamboo craftsmen in the Malang area of East Java as contemporary interior decoration products. Their condition is stagnant due to constraints in product development so the craftsmen are decreasing and there is no regeneration. In this study, the ceramic and bamboo crafts of craftsmen in Malang will be combined for contemporary interior decoration products. The results of this study are expected to be a product diversification and can provide design input for ceramic and bamboo craftsmen in Malang. Besides that, it can expand its market share and as a preservation of craft skills as a cultural heritage. This study uses the brainstorming design thinking method by combining two materials to create alternative products for ceramic and bamboo craftsmen in Malang. In addition, it can expand its market share and preserve craft skills as a cultural heritage. This research uses the design thinking method by applying ATUMICS theory to develop product design. This product's development utilizes existing ceramic moulds to speed up and reduce production costs. Likewise, the development of bamboo products, as well as the expertise that the craftsmen already have, adapted to a more modern form.